Estimation of tidal excursion length along the Shatt Al-Arab estuary, Southern Iraq - Lafta, Ali Abdulridha (Vietnam Journal of Science and Technology, 2021)
The tidal excursion length along the Shatt Al-Arab estuary was estimated based on the mathematical relation proposed by Parsa and Shahidi (2010). The field measurements of water level, bathymetry, and discharges were conducted to fulfill the objective of the study. The results revealed that the tidal excursion length is site-specific and depends on the characteristics of location which include tidal phases, bathymetry, and geometry. However, the results indicated that there are pronounced differences in tidal excursions lengths between the spring and neap tide phases in all studies stations. The spring tide coincided with the maximum tidal excursion lengths in Shatt Al-Arab estuary with 16.537, 16.187, 11.122, and 9.139 km in the estuary mouth, Faw, Siba, and Abo Flous stations respectively. While the neap tidal excursion lengths were 12.298, 9.254, and 7.269 km in Faw, Siba, and Abo Flous stations respectively.